1
$\begingroup$

Given a softmax function: $y_i = \frac{e^{z_i}}{\sum\limits_j e^{z_j}}$

With partial derivative: $\frac{\partial y_i}{\partial z_i} = y_i (1 - y_i)$

And a cross entropy function: $C = -\sum\limits_j t_j \log y_j$

Solve for $\frac{\partial C}{\partial z_i}$

My work so far:

\begin{align*} \frac{\partial C}{\partial y_j} &= -\frac{t_j}{y_j} \\ y_j &= e^{z_j - z_i} \cdot y_i \\ \frac{\partial y_j}{\partial z_i} &= e^{z_j - z_i} y_i(1-y_i) - e^{z_j - z_i}y_i \\ &= -y_i^2 e^{z_j - z_i} \\ \frac{\partial C}{\partial z_i} &= \sum\limits_j \frac{\partial C}{\partial y_j} \frac{\partial y_j}{\partial z_i} \\ &= \sum\limits_j \frac{t_j y_i^2 e^{z_j-z_i}}{y_j} \\ &= \sum\limits_j t_j y_i \\ &= y_i \sum\limits_j t_j \\ \end{align*}

The lecture slides give an answer of $y_i - t_i$. Why do my derivation steps not result in the same answer?

$\endgroup$
0
$\begingroup$

Are the $z_j$ functions of each other? In what follows I assume they are not (i.e. $\frac{\partial z_j}{\partial z_i}=0$ for all $i,j$ and derive a different answer from the one you gave. What about the $y_j$? Are the $t_i$ or the other $y_i$ functions of $y_j$?

If not, we have $\frac{\partial C}{\partial y_j}=-\frac{t_j}{y_j}$.

Also $y_j=e^{z_j-z_i}y_i$, so

$$\frac{\partial y_j}{\partial z_i}=e^{z_j-z_i}y_i(1-y_i)-e^{z_j-z_i}y_i=-y_i^2e^{z_j-z_i}$$ by the product rule. Thus

$$\frac{\partial C}{\partial z_i} = \sum_j \frac{\partial C}{\partial y_j} \frac{\partial y_j}{\partial z_i}=\sum_j \frac{t_jy_i^2}{y_j}e^{z_j-z_i}=\frac{y_i^2}{e^{z_i}}\sum_j\frac{t_je^{z_j}}{y_j}$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.